(3eTQhYjJg hCKQg Ydi GdMbhb hGdMQjGJ GdYGeI , OQGSI ebGQfI s - (3QGej eMehO(B, (3GdLGdjs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2019)
(3JWQb GdcJGH aj HGHg GdGhd Gdi GdJCKjQ GdGjLGHj ddUMGaI GdGdcJQhfjI Ydi GdMbhb h GdMQjGJ GdYGeI eJMOKG aj aUdg GdGhd Yf eGgjI MQjI GdJYHjQ Yf GdQCj GdYGe YHQ GdUMa GdGdcJQhfjI h GdVeGfGJ GdYGeI dMQjI GdJYHjQ Yf GdQCj h GdVeGfGJ GdNGUI HMQjI GdJYHjQ Yf GdQCj YHQ GdUMa GdGdcJQhfjI h GdMb aj GSJNOGe GSe eSJYGQ , GeG aj GdaUd GdKGfj aJfGhd eGgjI GdJfXje Gdegfj ddUMaj GdGdcJQhfj h Mb GdUMaj GdGdcJQhfj aj GdGfVeGe dfbGHI GdUMajjf , ajeG jNU GdHGH GdKGfj JMOK Mhd GdJCKjQ GdSdHj ddUMGaI GdGdcJQhfjI Ydi GdMbhb h GdMQjGJ GdYGeI haj GdaUd GdGhd JfGhd GdMjGI GdNGUI cbjO Ydi MQjI GdJYHjQ YHQ GdUMa GdGdcJQhfjI h eGgjI GdMb aj GdNUhUjI h GdeYWjGJ GdLOjOI ddMb aj GdNUhUjI aj eLGd GdfTQ GdUMaj GdGdcJQhfj , HjfeG aj GdaUd GdKGfj aJWQb Gdi MeGjI GdMb aj GdTQa h GdGYJHGQ cbjO Ydi MQjI GdUMa GdGdcJQhfjI h eGgjI LQGFe GdSH h GdbPa GdhGbYI YHQ GdUMa GdGdcJQhfjI h GjVG fXGe GdeSDhdjI GdLfGFjI Yf LQGFe GdSH h GdbPa GdhGbYI YHQ GdUMa GdGdcJQhfjI(B.s
(3HjHdjhZQGajG U(B.309s
Keywords: (3GdLQGFe GdEdcJQhfjIs; (3GdUMGaI GdGdcJQhfjIs; (3GdUMa GdGdcJQhfjI(B: (3MQjI GdJYHjQs; (3GdUMaj GdGdcJQhfj(B: (3GdJfXje Gdegfjs